Behavior of axially loaded high-strength steel circular hollow section tubes under low velocity lateral impact. (April 2023) - Cui, Guangming; Zhai, Ximei; Meng, Lingzhao
Abstract: High-strength steel has been widely used in large-span and high-rise structure engineering in recent years because it can improve the mechanical performance of building structures and reduce their self-weight. In this study, a lateral impact test using a drop hammer was conducted on 22 high-strength steel circular hollow section (CHS) tubes with axial preloading. The test parameters included the impact energy, tube diameter–thickness ratio, axial compression ratio, and shape of the hammerhead. The failure modes and entire impact process, including the impact force, displacement, strain, and axial force histories of the specimens, were obtained. A finite element (FE) model of the high-strength steel CHS tube preloaded by axial force (including compression and tension) under lateral impact was established using the nonlinear finite element analysis (FEA) software ANSYS/LS-DYNA. After verifying the accuracy of the FE model by comparison with the test results, a parameter analysis was conducted to reveal the influence of the impact energy, diameter–thickness ratio, axial compression ratio, axial force direction, and shape of the hammerhead on the dynamic response of the high-strength steel tube under lateral impact based on the test and FE results of the failure mode, impact force, displacement and energy histories, and residual stress. Highlights: Test data of high-strength steel CHS tubes under lateral impact are provided. The FEA is conducted to study the dynamic response of tubes under lateral impact. The influence of impact energy, axial compression ratio, etc. are investigated.